Toward green electrical discharge machining (EDM): state of art and outlook - Alrubaye, Israa Dheyaa Khalaf; Fantoni, Gualtiero (Machining science and technology, 2023)
The electrical discharge machining process is useful to manufacture complex shaped parts with high accuracy; however, it has unfriendly environmental impacts such as toxic emissions and health hazards; these impacts do not align with the recent orientation toward green industrial environments. Nowadays, researchers, practitioners, and designers focus on implementing sustainable EDM-based green environmental principles. Thus, this article presents an extensive overview of most of the enhancement and eco-friendly technologies for improving the efficiency of the EDM process (material removal rate, lower electrode wear ratio, and surface roughness) and lowering the environmental impacts. These enhancement technologies have been classified into four drivers. The advantages and limitations of each technology have been discussed. Then, the maturity of each technology has been estimated through technology readiness levels.